Pengendalian Safety Stock Guna meminimalkan Biaya Penyimpanan melalui Pendekatan Sistem Kanban Sebagai Pendukung Sistem Produksi Just In Time - Umar Wiwi; Eti Kristinawati (Department Industrial Engineering, University of Muhammadiyah Malang, 2002)
Based on ultimate goal of each company in gaining maximum profit with minimum total cost then one of alternative should be done in achieving this goal is avoiding excessive raw material stock resulting in high storage cost. The object of this research is CV. Pabrik Mesin Guntur Malang,an industrial water pumpcompany which is having difficulty in controlling raw material stock so that it often experiences abundant stocks.So,the problem is how to make stock controli n order to reduce stocks a mount that will result in storage cost reduction. Production S ystem Just in Time applying Karban system, that has been being implemented this far by Toyota Motor Corporation, Japan, is proposed to be implemented in that company as well in order to reduce prevailing inefficiency result from this existing problem. By applying Kanban system as support for the Production System Just in Time, it is shown that the system is capable in reducing stocka mount by 77.56%f or GTR type water pump and 89.59% for GTO type water pump. While reductions of storage cost achieved are78.99% for GTR type water pump and 90.45% for GTO tlpe water pump